Diagnostics and treatment of exocrine pancreatic insufficiency: clinical guidelines of the Russian gastroenterological Association - V. T. Ivashkin; I. V. Mayev; A. V. Okhlobystin; S. A. Alekseyenko; Ye. V. Beloborodova; Yu. A. Kucheryavy; T. L. Lapina; A. S. Trukhmanov; I. B. Khlynov; M. V. Chikunova; A. A. Sheptulin; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present the modern concept of etiology and pathogenesis of exocrine pancreatic insufficiency to general practitioners as well as with the established approach to diagnostics and treatment of this syndrome. Summary. Exocrine pancreatic insufficiency (EPI) develops if activity of the enzymes in duodenal lumen in response to meal stimulation is insufficient to maintain normal nutrient digestion. This state can develop primarily, due to various pancreatic diseases (chronic pancreatitis, pancreatic cancer, cystic fibrosis), and secondarily, due to impaired stimulation of pancreatic secretion or non-physiological conditions for activity of digestive enzymes. Basic manifestations of EPN the syndromes of maldigestion and malabsorption leading to development of nutritional failure. At the present time there is no standardized diagnostic method for estimation of pancreatic exocrine function, therefore there are no standard diagnostic criteria for EPN. In clinical practice EPN is diagnosed according to decreased fecal elastase activity in patients with verified pancreatic disease, which can cause decrease of pancreatic exocrine function. The basic EPN treatment method is pancreatic enzyme replacement therapy (PERT). For last 50 years there was an significant progress in development of PERT, numerous pancreatin-containing preparations were developed. Treatment of PERT require prescription of capsules, containing pancreatin microparticles protected by enteric coating. The highest evidential base at EPN is accumulated for pancreatin mini-microspheres. The starting dose of pancreatic enzymes for adults is 25 000 units of lipase per meal, which should be subsequently increased up to achievement of complete response confirmed by both clinical and laboratory scores. Digestive enzymes should be taken at the beginning of food intake, to increase treatment efficacy PERT should be accompanied by prescription of proton pump inhibitors. Patient’s diet quantity and content should be adjusted with participation of nutritionist. Patient should intake at least normal daily amount of fat and divide daily ration to at least six meals. Patients should be motivated to restrain from alcohol consumption and smoking as they can lead to further progression of pancreatic exocrine insufficiency and symptoms of pancreatitis.